HUBUNGAN TINGKAT KECUKUPAN GIZI, AKTIVITAS FISIK DAN KADAR HEMOGLOBIN DENGAN KEBUGARAN JASMANI (Studi pada Atlet Basket di Universitas Negeri Semarang) - Fannisa Mahastuti; M. Zen Rahfiludin; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
As the only University that has the Faculty of Sport Science in Semarang, the achievement of basketball team of the State University of Semarang (UNNES) was lower compared to other universities. Basketball games require good physical fitness. This study aimed to analyze the correlations between the level of nutritional adequacy, physical activity and hemoglobin levels with physical fitness in athletes basketball. This explanatory research was conducted in a cross sectional design. The population was all basketball athletes of UNNES (46 subjects). Thirty subjects were selected by purposive sampling. Data were collected by structured interviews, 2x24 hour food recall, 24 hours physical activity record, and hemoglobin by cyanmethemoglobin. Data were analyzed by Pearson Product Moment and Rank Spearman correlation tests. The results showed that the Energy Deficiency Rate was deficit in 44.3% of the subjects. Protein Adequacy was over the standard for 53.3% subjects. All of the subjects had low iron adequacy rate. Vitamin C adequacy was low in 83,3% subjects. Physical activity was heavy for 43.3%. Hemoglobin level was normal in 73,3% subjects. Good physical fitness was in 40% subjects. There was no correlations between Energy Deficiency Rate (p = 0,820), Protein Adequacy Rate (p = 0,735), vitamin C adeguacy (p = 0,325), and physical activity (0,273) with hemoglobin levels. There was a correlation between iron adequacy (p = 0.021) with hemoglobin level. Hemoglobin level (p = 0.001) was corrrelated with physical fitness. It is recommended that athletes crease their energy, iron, and vitamin C intakes to improve their physical fitness.